One-step trapping of droplets and surface functionalization of sensors using gold-patterned structures for multiplexing in biochips. Issue 68 (7th September 2017) - Dias, T. M.; Fernandes, E.; Cardoso, S.; Monteiro, G.; Freitas, P. P.
Abstract : A new methodology for one-step trapping of microspotted droplets and surface functionalization of sensors using gold-patterned structures for multiplexing Point-of-Care testing. Abstract : Multiplexing in Point-of-Care (POC) diagnostics is crucial for a comprehensive readout of multifactorial diseases such as cancer or fast-acting complications such as heart attacks. In multiplexed POC (MPOC) testing, groups of sensors are functionalized with different biological probes, enabling the simultaneous capture and detection of various analytes. Current literature demonstrates MPOC systems using microfluidics, capable of compartmentalizing only a few sensing regions. In contrast, miniaturized robotic spotting (microspotting) theoretically enables the independent functionalization of every sensor in a microarray. However, its use is still challenging in biosensors which require the combination of different materials at the surface because microspotted droplets tend to move to areas of higher surface energy, thus affecting the spotting precision. To counteract this phenomenon, we have combined shapes of gold-patterned films for the functionalization of magnetoresistive (MR) sensors and simultaneous trapping of droplets over the sensing regions, previously passivated with silicon nitride (Si3 N4 ). Due to the higher hydrophobicity of gold when compared to Si3 N4, the droplets remain immobilized inside the gold frames and functionalization of the sensors is accurately achieved. With this strategy, we demonstrate the microspotting of different DNA probes and antibodies and the specific hybridization and binding of complementary DNA targets and proteins, attached to magnetic beads. This combined trapping and functionalization system shows promise in the implementation of MR-based systems in multiplexing applications. This work can also be of interest to the wider community working in the development of other surface-based assays, also developed through microfabrication techniques, as the same trapping methodology is conceivable for adaption to other biochip formats.